Letter to Editors - Manandhar, Dhruba Narayan (Journal of Agriculture and Environment, 2013)
Mr. Dhruba Narayan Manandhar (Pest and Pesticide Management Expert, phone 4429604) writes to the Editor-in-Chief regarding an article entitled 'Knowledge, practice and use of pesticides among commercial vegetable growers of Dhading district, Nepal' published in The Jou. of Agri. and Env., vol.11 (2010), pp. 95-100. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 148 DOI: http://dx.doi.org/10.3126/aej.v12i0.7575